ANALISIS SPARE PART HARBOUR TAG PADA DIVISI WORKSHOP MENGGUNAKAN ALGORITMA KNN MIN-MAX SCALING - Oloan Sihombing; Edwin Sitanggang; Erik Luis; Kevin Wilmar Winata (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This study aims to simplify and assist the workshop division in making decisions regarding the amount of stock that must be prepared in large quantities by PT. Multi Jaya Samudera which is a company engaged in shipping services. This study discusses the prediction of supply of ship spare parts which are very important for the workshop division. If spare parts are not available it can hamper the ship's operations which will result in delays in ship repairs and reduce work efficiency. The data used in this study is data for 2021 where the data to be tested is 225 data from the data tested can be used as a guide for planning spare parts inventory. The method used is K-Nearest Neighbor (KNN) which produces an accuracy of 93.33%. The results of the application of the KNN Min-Max scaling method can help and facilitate companies in supplying ship spare parts so that they do not hinder ship operations.